Base seismic isolation of a historical masonry church using fiber reinforced elastomeric isolators. Issue 120 (May 2019) - Habieb, Ahmad Basshofi; Valente, Marco; Milani, Gabriele
Abstract: This paper investigates the possibility of improving the seismic performance of a small historical masonry church using fiber reinforced elastomeric isolators in bonded (BFREI) and unbonded (UFREI) applications. Detailed three-dimensional (3D) finite element (FE) models are used to characterize the behavior of the two types of FREIs. An Abaqus User Element (UEL) is developed to simulate the 3D behavior of FREIs for large scale seismic analyses of complex isolated structures. The results of cyclic shear analyses show that the proposed UEL model can accurately predict the FREIs behavior obtained through detailed 3D FE models. A series of non-linear dynamic analyses are performed to investigate the seismic response of a small historical masonry church in the original and base-isolated configurations employing both BFREIs and UFREIs. Numerical results show that the fixed-base model of the church experiences severe and widespread damage, while UFREIs are found to be effective in significantly reducing the damage level of the church when subjected to moderate-to-high seismic actions. Moreover, it can be observed that both the isolator types satisfy the maximum lateral displacement requirements reported in the literature. Highlights: Base seismic isolation of historical masonry church with elastomeric isolators. Non-linear dynamic analyses NLADA conducted through full 3D FE models in ABAQUS. fiber reinforced elastomeric isolators in bonded (BFREI) and unbonded (UFREI) configuration. Abaqus User Element (UEL) to represent the 3D behavior of FREIs for global seismic analyses. Detailed 3D FE models to characterize FREI cyclic behavior.